2014
DOI: 10.1111/bdi.12215
|View full text |Cite
|
Sign up to set email alerts
|

A five‐year follow‐up study of neurocognitive functioning in bipolar disorder

Abstract: Cognitive dysfunction that is characteristic of bipolar disorder is persistent and stable over time. Only dysfunction in verbal recall was found to show a progressive course that cannot be explained by clinical or treatment variables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
69
2
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(77 citation statements)
references
References 59 publications
4
69
2
2
Order By: Relevance
“…1). Consistently, in a five-year follow-up study of neurocognitive functioning in BD, a dysfunction in verbal memory became more evident in patients at late stages (Santos et al, 2014). In addition, our study showed that only subjects at later stages of illness present worse semantic clustering scores as compared to controls.…”
Section: Discussionmentioning
confidence: 63%
“…1). Consistently, in a five-year follow-up study of neurocognitive functioning in BD, a dysfunction in verbal memory became more evident in patients at late stages (Santos et al, 2014). In addition, our study showed that only subjects at later stages of illness present worse semantic clustering scores as compared to controls.…”
Section: Discussionmentioning
confidence: 63%
“…Performance by bipolar participants on this task was equally mixed between scores that were similar to, or lower than controls (Bonnin et al, 2012; Marshall et al, 2012; Martino et al, 2011a,b, 2014; Ryan et al, 2013; Torrent et al, 2006) (Ancin et al, 2013, 2010; Elshahawi et al, 2011; Martinez-Aran et al, 2009, 2007; Sanchez-Morla et al, 2009; Santos et al, 2014; Torrent et al, 2011). Among relatives intelligence was shown to be mostly preserved when tested using this task (Antila et al, 2009; Christodoulou et al, 2012; Daban et al, 2012; Doyle et al, 2009; Fears et al, 2014; Quraishi et al, 2009; Schulze et al, 2011; Thermenos et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…In BD a decreased neuropil, with resulting disturbances of microconnectivity, may inhibit information flow from the hippocampus to the cortex and subcortical structures and contribute to the cognitive symptoms of the disorder. Indeed, patients with BD have deficits in hippocampusrelated cognitive tasks such as verbal memory (Hsiao et al 2009;Bora et al 2010) and one study found progressive worsening in verbal recall over a five-year follow-up period that could not be explained by effects of acute episodes or treatment (Santos et al 2014).…”
Section: Discussionmentioning
confidence: 99%